2021
DOI: 10.5547/01956574.42.2.mpro
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Gas Announcement Day Puzzle

Abstract: This paper studies natural gas futures returns on EIA storage announcement days.More than 50% of the annual return is earned on these days. We find a significant difference between announcement and non-announcement day returns, which cannot be explained by the announcement surprise or other control variables. At the intraday level, the return splits half into a pre- and post-announcement part. The pre-announcement return is entirely generated on days when storage levels exceed analysts’ expectations casting do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
3
2
Order By: Relevance
“…Apparently, the storage announcement leads traders to reassess the implications of other information thereby producing much larger price movements than on other days. Some prior literature (e.g., Chiou-Wei et al, 2014;Prokopczuk et al, 2021) also suggested that RNG W should differ on announcement days, implying that I 0 should be significant in the mean equation, but we found only I 3 significant. We do not have a good explanation for this result.…”
contrasting
confidence: 68%
See 4 more Smart Citations
“…Apparently, the storage announcement leads traders to reassess the implications of other information thereby producing much larger price movements than on other days. Some prior literature (e.g., Chiou-Wei et al, 2014;Prokopczuk et al, 2021) also suggested that RNG W should differ on announcement days, implying that I 0 should be significant in the mean equation, but we found only I 3 significant. We do not have a good explanation for this result.…”
contrasting
confidence: 68%
“…Some prior literature (e.g., Chiou‐Wei et al, 2014; Prokopczuk et al, 2021) also suggested that RNG W should differ on announcement days, implying that I 0 should be significant in the mean equation, but we found only I 3 significant. We do not have a good explanation for this result.…”
Section: Rng and Its Variancecontrasting
confidence: 44%
See 3 more Smart Citations